Metode Pembelajaran Rasulullah dalam Perspektif Hadits Tarbawi: Studi Analisis Pedagogis terhadap Strategi Edukatif Nabi - Ikat Sutriani; Faqihuddin Akbar Mu'allim; Ainul Gani; Muhammad Akmansyah; Amirudin Amirudin (Paedagogie, 2026)
The dominance of technocratic”“cognitive approaches in modern education often neglects the spiritual dimension and exemplary conduct as essential elements in the learning process. This study aims to analyze the teaching methods of the Prophet Muhammad from the perspective of hadith tarbawi, highlighting the Prophet’s educational strategies as a model of Islamic pedagogy that is relevant to contemporary education. This research employs a qualitative approach using a library research design. The data were obtained from hadith tarbawi that describe the educational practices of the Prophet Muhammad, as well as relevant literature on Islamic education, and were analyzed using thematic analysis techniques. The results show that the teaching methods of the Prophet Muhammad possess integrative, humanistic, and contextual characteristics. These are reflected in several key strategies, namely exemplary conduct (uswah), interactive dialogue (hiwar), gradual learning (tadarruj), the use of stories and parables, strengthening spiritual motivation (targhib wa tarhib), and differentiated instruction according to students’ characteristics. These strategies shape a holistic educational process that balances cognitive, affective, and psychomotor aspects. This study concludes that the teaching methods of the Prophet Muhammad hold epistemological and practical significance for contextualization within modern educational systems that emphasize character formation and the strengthening of spiritual values in the learning process.